DETERMINATIONOF TRACE NITRITEAS 4-(4-NITROBENZENAZO)- 1-AMINONAPHTHALENE COMPLEX BY EXTRACTION-5PECTROPHOTOMETRY Metode Penentuan Nitrit sebagal Kompleks 4-(4-Nitrobenzenazo)-1-Amlnonafta/en secara ... - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2009)
ABSTRACT A study of extraction-spectrophotometricmethod for the determination of trace nitrite as 4-(4-nitrobenzenazo)- 1-aminonaphthalenecomplex using n-amylalcoholand chloroformas organic solvents has been done. Results of the study showed that extraction-spectrophotometricdeterminationof nitrite using n-amylalcoholor chloroform was very sensitive and had low limit of detection. Extraction-spectrophotometricmethod of nitrite using n-amylalcohol gave range of linear concentration 0.000-0.054 mg/L N02--N, detection limit of 2.09x10-4mg/L N02--N, and sensitivity of 34.514 :i: 0.398 absorbance unit per mg/L of N02--N. Meanwhile, extraction-spectrophotometricof nitrite using chloroform had range of linear concentration of 0.000-0.100mg/L N02--N,detection limit of 8.99x10-4mg/L NOi-N, and sensitivity of 18.353:i:0.456 absorbance unit per mg/L NOi-N. Keywords: Nitrite Trace, 4-(4-Nitrobenzenazo)-1-Aminonaphtha/ene, Extraction-Spectrophotometry